Rational designed hierarchical dual carbon protected ZnSe anode for advanced sodium-ion hybrid capacitors. (25th August 2022) - Zhang, Litong; Zhao, Hongan; Dai, Liming; Yao, Fanglei; Huang, Yin; Xue, Wenkang; Zhu, Junwu; Sun, Jingwen
Abstract: With a remarkable advantage of high theoretical capacity and excellent rate performance, zinc selenide (ZnSe) has been regarded as a high-potential electrode for sodium-ion batteries (SIBs). Nevertheless, the practical use of ZnSe as the anode for SIBs is severely limited by the large volumetric expansion and sluggish kinetics during the conversion/alloying reaction process. Herein, we develop a dual-type carbon approach to afford a 3D hierarchical ZnSe@N-doped carbon/reduced graphene oxide (ZnSe@NC/rGO) using simple selenization of ZIF-8 and subsequent incorporation process. Alongside with buffering the volume variation by the in-situ generated NC, the electron and ion transfer can also be accelerated on account of the interconnected graphene network. Therefore, the ZnSe@NC/rGO offers a splendid discharge capacity of 455.3 mAh g −1 at 0.1 A g −1, and exhibits a superior rate capability of 195.1 mAh g −1 at 5 A g −1 . Besides, the capacity retains as high as 170.1 mAh g −1 after 500 cycles at 5 A g −1, indicating an outstanding cyclic ability. A full-cell sodium ion hybrid capacitor (SIHC) constructed using a ZnSe@NC/rGO anode and a commercial activated carbon (AC) cathode (ZnSe@NC/rGO//AC SIHC) shows a high energy output of 117.8 Wh kg −1 at 105 W kg −1, and a long lifespan with 86.4% capacity retention over 3000 cycles. Graphical abstract: Unlabelled Image Highlights: A superior and stable ZnSe anode is synthesized through a dual-type carbon protection strategy. The ZnSe@NC/rGO electrode shows a superior sodium storage performance. EIS and GITT technologies confirm the rapid Na mobility of ZnSe@NC/rGO electrode. The as-assembled SIHC exhibits high energy/power densities of 117.8 Wh kg −1 /4200 W kg −1 .